Field and petrographic studies of granite from Pulau Jarak and Pulau Sembilan, Peninsular Malaysia - A. Ghani, Azman (Malaysian Journal of Science, 2008)
Jarak and Sembilan islands are the westernmost islands off the mainland of Peninsular Malaysia. Both islands are underlain by granitic rock. Field and textural characteristics of the granites are similar to the tin bearing Main Range granite of Peninsular Malaysia. Structural features such as occurrence of tourmaline pods, accumulation of the large pegmatitic K-feldspar and occurrence of aplopegmatite complex suggest that the granite magma is highly evolved. Both islands are made up of porphyritic to coarse grained biotite granite. The grain size of K-feldspar phenocryst can be up to 4 cm across. The granite is made up of quartz (35%), plagioclase (19%), K-feldspar (43%), biotite (4.5%) and can be classified as monzogranite to syenogranite. Subhedral to anhedral biotite is the main mafic phase. The granitic rocks from Jarak and Sembilan occupy a central area of the QAP diagram. Granites plotting in this area have been regarded as crustal melts and this suggests the importance of crustal material in the source rocks of those plutons. The importance of crustal material in the source rock is supported by the occurrence of metasedimentary enclave. This may suggest that the Jarak and Sembilan magmas are derived from partial melting of the sedimentary rock e.g. pelitic rocks.